ANALISIS STABILITAS LERENG DI JALAN AHMAD YANI NO. 49, KOTA SORONG MENGGUNAKAN SOFTWARE ROCSLIDE - Islami, Anisul; Saputra, Asrul Saputra; Puspa Rini, Retno; Rokhman; Januar Jafaruddin, Ahmad (Universitas Muhammadiyah Sorong, 2024)
Vihara Budha Jayanti which is one of the natural attractions and is also a place of worship of Buddhists in the city of sorong which is geographically located on hills that have the potential for landslides because the slope of the area is included in the steep category with a slope angle of 51°. The purpose of this study was to evaluate the slope stability of the most potential landslide areas in the area. Slope stability analysis was done manually or using Rocslide software with Fellenius method as a comparison to determine the lowest safety factor in critical collapse areas. In this analysis, input data of soil parameters from the laboratory, such as the weight of the soil, cohesion and the angle of friction are needed. Based on the results of the analysis obtained safety factor (SF) slopes in saturated conditions using Rocslide software of 0,85 (SF < 1,25) and manual calculation of 0,60 (SF < 1,25). From these two calculations it can be concluded that unstable slopes or landslides are common because the value of the safety factor (FS) < 1,25.